Provision of Infracstructure as a Strategy towards Rural Development: A Comparative Analysis of Gbongan, Akiriboto, Osu and Ibodi - Akeredolu, Oluwapelumi Kolawole (Obafemi Awolowo University, 2014)
This study examines the impact of the provision of infrastructure in the socio-economic development of rural areas. The study attempt to test the proposition that the degree of development has a positive relationship with the level of provision of infrastructure. The study focuses on Gbongan, Akiriboto, Osu and Ibodi in Oyo State of Nigeria. Original survey materials and secondary data were used to show that the degree of development in the rural areas is a function of the provision of such infrastructures as transport, communications and power as well as agricultural and health services. The policy implications of the findings were considered in the concluding sections of the thesis. Further, it is the contention of the thesis that Government interventions in rural development should therefore revolve round the provision of infrastructures that will enhance agricultural development and communal level of living' in order to stem rural-urban migration.